Selective harmonic eliminated V/f speed control of single-phase induction motor - Duranay, Zeynep Bala; Guldemir, Hanifi (Inst Engineering Technology-Iet, 2018)
This study presents a new energy efficient V/f speed control of single-phase induction motor. The method is implemented with a single-phase inverter in which extreme learning machine technique is used to achieve selective harmonic elimination pulse width modulation. The objective is to adjust the speed of the single-phase induction motor while eliminating undesired low-order harmonics. Algorithm is developed using MATLAB/Simulink high-speed adaptation was obtained even at low- and high-speed regions. The results showed the effectiveness of the proposed method. The reduction in the total harmonic distortion is achieved in all operation range of V/f speed control.
Keywords: induction motors; machine control; angular velocity control; harmonic distortion; PWM invertors; power conversion harmonics; learning (artificial intelligence); selective harmonic eliminated V; f speed control; single-phase induction motor; energy efficient V; f speed control; single-phase inverter; extreme learning machine technique; selective harmonic elimination pulse width modulation; speed adjustment; undesired low-order harmonics elimination; MATLAB-Simulink high-speed adaptation; low-speed regions; high-speed regions; total harmonic distortion